From training to learning in enterprise resource planning systems. (15th March 2012) - Kerr, Don; Murray, Peter A.; Burgess, Kevin
The information systems' literature outlines how training is a critical factor to successful Enterprise Resource Planning (ERP) implementations. Yet, types of training are not discussed in the literature and there is little indication if existing training is effective and whether relevant contextual factors have been considered. Without understanding how learning is connected to training processes and outputs, answers related to which training frameworks are required for successful ERP implementation are difficult to determine. Using a case study approach, this study finds that traditional ERP training is too focused on a methodical learning culture that restricts the effectiveness of training. While the importance of methodical learning is outlined, it is posited that emergent learning behaviour is much more likely to improve the overall effectiveness of ERP training and implementation.